Integration of Mobile Assisted Language Learning in Arabic Language Education: A Systematic Literature Review - Nurazizah, Ai; Aedi, Khasan; Wahyudin, Wahyudin (Journal of Language and Literature Studies, 2026)
Arabic language learning in Indonesia is facing a critical transformation in the 21st century, shifting from conventional teacher-centered models to technology-integrated ecosystems. Despite the potential of mobile technology, there is a significant gap in empirical validation regarding which specific applications are effective and how they can be pedagogically integrated within the Indonesian curriculum . This study aims to fill this gap by identifying prior research, analyzing the effectiveness of mobile applications, and providing evidence-based recommendations for Arabic language educators. This study employs a Systematic Literature Review (SLR) design following the PRISMA framework. Data were systematically retrieved from DOAJ and Semantic Scholar databases using PICOS criteria and strictly limited to the 2021-2025 publication period. Study quality was rigorously assessed using the Mixed Methods Appraisal Tool (MMAT). The findings reveal that mobile applications significantly enhance learning outcomes, particularly in vocabulary retention, motivation, and specific skills such as reading, listening, and vocabulary mastery. Key tools identified include Lectora Inspire, Duolingo, Memrise, and Plotagon Studio. The study concludes that while highly effective, implementation is hindered by technical barriers and low teacher digital competency. Practical implications suggest that for direct classroom application, educators must transition from traditional models to facilitator roles, integrating gamified features like leaderboards and interactive feedback to foster student engagement . Furthermore, successful integration requires curriculum-aligned content and the adoption of offline-capable applications to bridge the digital divide in diverse educational settings.